Seal remains as sources of mercury forAntarctic environment - Zvěřina, O.; Coufalík, P. (Pavel); Brat, K.; Červenka, R.; Kuta, J.; Mikeš, O.; Komárek, J. (2016)
The northern part of James Ross Island (Antarctica) presents a location with an unusual occurrence of seal carcasses. The main goal of this study was to estimate importance of this mercury source and mercury fate in the environment. The contents of mercury in underlying soils were found to be up to five times higher than the background levels. Methylmercury formed up to 2.8% of total mercury. According to the results, seal remains represent a clear source of mercury in the observed area.